Catalytic olefin epoxidation with a carboxylic acid-functionalized cyclopentadienyl molybdenum tricarbonyl complex - Gomes, Ana C.
The complex CpMo(CO)(3)CH2COOH (1) (Cp = eta(5)-C5H5) has been examined as a precatalyst for the epoxidation of cis-cyclooctene and alpha-pinene using tert-butylhydroperoxide (TBHP) as oxidant. A high turnover frequency of ca. 600 mol mol(Mo)(-1) h(-1) was achieved in the epoxidation of cyclooctene, giving the epoxide as the only reaction product. With alpha-pinene as substrate, the added-value products a-pinene oxide and campholenic aldehyde were obtained. Two different approaches to facilitate catalyst recovery and reuse were explored: (1) use of an ionic liquid (IL) as solvent, and (2) intercalation of 1 in a Zn, Al layered double hydroxide (LDH) by a direct synthesis (coprecipitation) route. Characterization of the LDH by powder X-ray diffraction, thermogravimetric analysis, FT-IR and C-13 CP MAS NMR spectroscopies showed that the CpMo(CO)(3)CH2COO- anions intercalate in a bilayer arrangement, resulting in an interlayer spacing of 20.7 angstrom. In the epoxidation of cyclooctene, catalytic activity in the first batch run was very high for the catalyst/IL mixture and moderate for the LDH. Characterization of the LDH after catalysis indicated that nearly complete oxidative decarbonylation of supported complexes had occurred (by reaction with TBHP), resulting in the presence of immobilized oxomolybdenum species. However, catalytic activities for both the recovered LDH and catalyst/IL decreased in consecutive runs, due in part to progressive removal of active species during either the catalytic reaction (for the LDH) or the solvent extraction/work-up (for the catalyst/IL mixture). (C) 2013 Elsevier B.V. All rights reserved.